(untitled) (Global Journal of Human-Social Science, 2023)
The article analyzes the implicit aspects of G Hegel s doctrine of sublation It is shown that the negation of negation the result of which is dialectical sublation was often treated superficially in the progressivist-revolutionary tradition It is emphasized that when sublated it is very important to preserve the content that at first glance is negated Negation is not to be understood as rejection The doctrine of dialectical sublation is compared with some paradoxical aspects of O Mandelstam s worldview which are most clearly expressed in the poem Lamarck The question about the truth of simplification involution is raised